Dampak Kondisi Fisik pada Tendangan Sabit dalam Olahraga Pencak Silat - Ali Mardius; Eri Barlian; Nurul Ihsan (Universitas Pendidikan Ganesha, 2023)
Sickle kick is a Pencak silat martial arts technique that athletes must master to gain match points. It is just that the reality on the ground shows that the crescent kick technique shown by athletes could be more optimal. The flexibility of the waist and the reaction speed is one factor that determines the success of an athlete's kick. This study aimed to determine the effect of waist flexibility and the speed of reaction to sickle kicks by Perisai Diri pencak silat athletes. This research belongs to quantitative research using a correlation design with causal associative methods. The population in this study was 35 people. The sample was taken using the probability sampling technique, with the final sample size being 35 people. Data was collected using measurements of the three variables. The flexibility of the waist was tested with a flexiometer. The reaction speed was a whole-body reaction. In contrast, a sickle kick ability test measured the crescent kick ability. Data were analyzed with two predictors and multiple regression. Based on the data analysis results, waist flexibility has a significantly positive effect on the accuracy of sickle kicks, and reaction speed has a significantly positive effect on the accuracy of sickle kicks. Based on these results, it can be concluded that waist flexibility and reaction rate significantly positively affect the accuracy of sickle kicks of Pencak Silat Perisai Diri athletes.